Intellectual property rights hinder sequential innovation: Experimental evidence - Julia Brüggemann; Paolo Crosetto; Lukas Meub; Kilian Bizer (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2015)
In this paper we contribute to the discussion on whether intellectual property rights foster or hinder innovation by means of a laboratory experiment. We introduce a novel Scrabble-like creativity task that captures most essentialities of a sequential innovation process. We use this task to investigate the effects of intellectual property allowing subjects to assign license fees to their innovations. We find intellectual property to have an adversely effect on welfare as innovations become less frequent and less sophisticated. Communication among innovators is not able to prevent this detrimental effect. Introducing intellectual property results in more basic innovations and subjects fail to exploit the most valuable sequential innovation paths. Subjects act more self-reliant and non-optimally in order to avoid paying license fees. Our results suggest that granting intellectual property rights hinders innovations, especially for sectors characterized by a strong sequentiality in innovation processes.
Keywords: C91; D89; K39; 330; innovation; intellectual property; laboratory experiment; real effort task; creativity